Implementasi Model Pembelajaran TTW Berbantuan Media Cerpen dalam Meningkatkan Keterampilan Menulis Puisi - Wahyuni, Riska; Turistiani , Trinil Dwi; Rahma , Diana Esmeralda (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This research has a background of students who experience difficulties in developing ideas when writing poetry. The aim of the research is to improve poetry writing skills and improve learning outcomes for poetry writing skills using the TTW (Think Talk Write) learning model assisted by short story media. This research is a type of Collaborative Classroom Action Research (PTKK) in accordance with the stages of lesson study activities. The research was carried out in two learning cycles using observation data collection techniques and documentation of results. The subjects in this research were 28 participants in class VIII-F of SMP Negeri 34 Surabaya. The results of this research show an increase in the poetry writing skills of class VIII-F students from the two cycles carried out. Students obtained an average score in the 1st cycle of 62 and in the 2nd cycle of 87.5. These data show that there is an increase in student learning outcomes in poetry writing skills.